Semantic study: Polysemi in arabic form of verb and noun - Cinta, Fitria; Irawan, Bambang; Hasan, Nur (Universitas Lampung, 2023)
In semantic studies, there is a relationship between words and meaning. However, language learners often experience difficulties in assigning meaning to a word or sentence. The purpose of this research is to find out in depth about polysemy, the causes of its occurrence and examples of polysemy in verb and noun forms. This research uses descriptive qualitative method. Data collection techniques use library research using journals and books that are relevant to the discussion. Data analysis techniques use the relevant data collection stages, data reduction, grouping and selecting the necessary data, then providing temporary conclusions and verifying the data. The final stage is data collection and data presentation systematically (data display). The results of this study are polysemy is a relationship between words that are often used in several sentences or different contexts, or can be interpreted as a word that has more than one meaning. So that polysemy has a basic meaning and a derived meaning. The main causes of polysemy are; (1) dialect development (2) figurative language, (3) sharaf rules, (4) mixing of other languages and (5) language development. Polysemy can occur as nouns and verbs. Words that contain polysemy meaning can occur in noun and verb forms. An example of polysemy is the noun يد which has many meanings, including hands, help/power/strength, thief, power/will, guidance, giver, cash (cash) and virtue/kindness. The word وجه has many meanings including face, beginning/beginning, surrender, not feeling humiliated, right, actually, absolutely, substance, apostasy and equality. The word قام in the Qur'an has many meanings, including standing, implementing, replacing and held. The verb نصر when experiencing derivation has many meanings including helping, being Christian, helping each other, winning and asking for help.